Perspectives on resilience for military readiness and preparedness: Report of an international military physiology roundtable. Issue 11 (November 2018) - Nindl, Bradley C.; Billing, Daniel C.; Drain, Jace R.; Beckner, Meaghan E.; Greeves, Julie; Groeller, Herbert; Teien, Hilde K.; Marcora, Samuele; Moffitt, Anthony; Reilly, Tara; Taylor, Nigel A.S.; Young, Andrew J.; et al.
Abstract: Modern warfare operations often occur in volatile, uncertain, complex, and ambiguous (VUCA) environments accompanied by physical exertion, cognitive overload, sleep restriction and caloric deprivation. The increasingly fast-paced nature of these operations requires military personnel to demonstrate readiness and resiliency in the face of stressful environments to maintain optimal cognitive and physical performance necessary for success. Resiliency, the capacity to overcome the negative effects of setbacks and associated stress on performance, is a complex process involving not only an individual's physiology and psychology, but the influence of factors such as sex, environment, and training. The purpose of this moderated roundtable was to address five key domains of resiliency in a point/counterpoint format: physiological versus psychological resiliency, sex differences, contributions of aerobic and strength training, thermal tolerance, and the role of nature versus nurture. Each speaker was given three minutes to present and the moderator facilitated questions and discussion following the panel's presentation. The interconnectedness of the five domains highlights the need for an interdisciplinary approach to understand and build resilience to enhance military performance.